1997
DOI: 10.1002/1521-396x(199707)162:1<199::aid-pssa199>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep Defect Centers in Silicon Carbide Monitored with Deep Level Transient Spectroscopy

Abstract: Electrical data obtained from deep level transient spectroscopy investigations on deep defect centers in the 3C, 4H, and 6H SiC polytypes are reviewed. Emphasis is put on intrinsic defect centers observed in as‐grown material and subsequent to ion implantation or electron irradiation as well as on defect centers caused by doping with or implantation of transition metals (vanadium, titanium, chromium, and scandium).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
264
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(291 citation statements)
references
References 33 publications
22
264
1
4
Order By: Relevance
“…It was observed that defect E 0.39 disappeared after leaving the sample at room temperature for a week, showing that the defect was not stable at room temperature. The deep level defects E 0.62 and E 0.65 have been previously reported to be defects composed of several energy levels commonly referred to as the Z 1 /Z 2 [16,[26][27][28][29].…”
Section: Deep Level Transient Spectroscopy Analysismentioning
confidence: 99%
“…It was observed that defect E 0.39 disappeared after leaving the sample at room temperature for a week, showing that the defect was not stable at room temperature. The deep level defects E 0.62 and E 0.65 have been previously reported to be defects composed of several energy levels commonly referred to as the Z 1 /Z 2 [16,[26][27][28][29].…”
Section: Deep Level Transient Spectroscopy Analysismentioning
confidence: 99%
“…In both spectra, the well-known intrinsic defects Z 1/2 (Ref. 20) and EH6/7 (Ref. 21) were observed.…”
Section: A Fe In N-type 4h-sicmentioning
confidence: 99%
“…HEE irradiation induces defects in SiC. [17][18][19] Some defects may lead generation recombination current leading to higher ideality factors. Fig.…”
Section: I-v Resultsmentioning
confidence: 99%